(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2021)
Global cities have historically been the symbolic meeting place of the longstanding relationship between immigration and globalization. But the pandemic has challenged this historic relationship. The virus has had an unprecedented impact on global economic immigration, it has altered the dynamics of international population movements. Global cities, never so dark and silent, are the iconoclastic representations of the crises produced by the health emergency. The concept of space and time changes in the international geopolitical landscape, but also in everyday life, from homes to offices, from city streets to the suburbs. Faced with the “network of bits” that connect everything, passing beyond physical borders, the architecture of the cities, the places of life and work is destined to adapt to new urban planning and new ideas of living space. The aim of this paper is to analyse from a geopolitical perspective the evolution of urban space in the new post-pandemic normality in a glocal world.